RAGAM ASESMEN DALAM PEMBELAJARAN BERDIFERENSIASI - Zahro, Amanda Lailatus; Nurdiana, Fany Meta; Melati, Nadia Vita; Setyaningsih, Sri Wahyu; Mahdiyah, Syarifah; Listiani, Welas (Jurnal Pendidikan Matematika Malikussaleh, 2025)
Differentiated learning is an approach that adapts the learning process to the needs, interests, and characteristics of students. In its implementation, assessment plays an important role in identifying students' learning needs and evaluating the effectiveness of differentiated learning. This study uses a literature study method or literature review, researchers collect data and information from various previous sources that are in accordance with the title "Various Assessments in Differentiated Learning" including articles, journals, books, and other literature reviews. The results of the study in this article show that assessments consist of three types, namely diagnostic, formative, and summative assessments. Diagnostic assessments are used to analyze students' learning readiness, formative assessments are used during learning to see learning developments and adjust learning strategies, while summative assessments are used to measure students' final achievementsThis study confirms that the selection and implementation of appropriate assessments in differentiated learning can increase the potential for student learning success.